Extracorporeal Life Support After Cardiac Surgery in Children: Outcomes From a Single Institution. Issue 1 (14th October 2013) - Sasaki, Takashi; Asou, Toshihide; Takeda, Yuko; Onakatomi, Yasuko; Tominaga, Takashi; Yamamoto, Yusuke
Abstract Extracorporeal life support (ECLS) is used after congenital heart surgery for several indications, including failure to separate from cardiopulmonary bypass, postoperative low cardiac output syndrome, and extracorporeal cardiopulmonary resuscitation. Here, we assessed the outcomes of ECLS in children after cardiac surgery at our institution. Medical records of all children who required postoperative ECLS at our institution were reviewed. Between 2003 and 2011, 36 (1.4%) of 2541 pediatric cardiac surgical cases required postoperative ECLS. Median age of patients was 64 days (range: 0 days–4.1 years). ECLS was in the form of either extracorporeal membrane oxygenation (ECMO; n = 24) or ventricular assist system (VAS; n = 12). Mean duration of ECLS was 4.9 ± 4.2 days. Overall, 21 patients (58%) were weaned off ECLS, and 17 patients (47%) were successfully discharged from the hospital. Patients with biventricular heart (BVH) had higher survival‐to‐hospital discharge rates compared with those with univentricular heart (UVH) (P = 0.019). Regarding ECLS type, UVH patients who received VAS showed higher rates of device discontinuation than UVH patients who received ECMO (P = 0.012). However, rates of hospital discharge were not significantly different between UVH patients who received VAS or ECMO. Surgical interventions, such as banding of Blalock–Taussig shunt to reduce pulmonary blood flow or placing bidirectional cavopulmonary shunt to minimize ventricular volume overload, were effective for weaning off ECLS in patients with UVH. ECLS is beneficial to children with low cardiac output after cardiac surgery. Rates of survival‐to‐hospital discharge were higher in BVH patients than UVH patients. Additional interventions to reduce ventricular volume load may be effective for discontinuing ECLS in patients with UVH.